Pharmacogenetic implications in the management of metabolic diseases in Brazilian populations - Rosario Dominguez Crespo Hirata; Alvaro Cerda; Fabiana Dalla Vecchia Genvigir; Mario Hiroyuki Hirata (Universidade de São Paulo, 2018)
Dyslipidemia, diabetes, obesity and hypertension are common metabolic diseases. In the last decades, unhealthy lifestyle and aging have leads to an increased incidence of these diseases, increasing morbidity and mortality by cardiovascular causes. The treatment of metabolic diseases includes life-style interventions as healthy diet and physical exercise, as well as pharmacological interventions. Several drugs are available for the management of metabolic diseases including among others lipid-lowering antidiabetics and antihypertensive drugs. Variability in response to these drugs is influenced by both genetic and non-genetic factors. Polymorphisms in genes related to drug pharmacokinetics and pharmacodynamics have been shown to influence drug efficacy and safety. This review is focused on pharmacogenetic studies related to the management of metabolic diseases in samples of the Brazilian population. Associations of variants in drug metabolizing enzymes and transporters, drug target and metabolism-related genes with the efficacy and safety of lipid-lowering, antidiabetic and antihypertensive drugs are described. Most pharmacogenetic studies in Brazil have focused in pharmacological response to a small group of drugs, as statins and some antihypertensives, while there are almost no studies on antidiabetic and antiobesity drugs. Some studies reported significant associations of gene polymorphisms with drug response confirming previous data from other populations, whereas other works did not replicate, which may relay on the genetic admixture of our population. In conclusion, further studies are necessary considering larger sample sizes, new unexplored drugs and more genetic variants to obtain stronger conclusions to explore clinical applications of pharmacogenetic studies in our population.